2020
DOI: 10.1007/s13201-019-1132-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and frequency analysis of flooding solid flow in semi-arid zone: case of Mekerra catchment in the north-west of Algeria

Abstract: In this study, we evaluate the soil erosion and solid transport in the oued Mekerra watershed in north-west Algeria. The study area is subject to a semi-arid climate characterized by irregular rainfall and showers, which are often accompanied by significant floods. These floods of large volumes transport large amounts of solid input to the Sarno dam, which is in the outlet of oued Mekerra. Therefore, the water storage capacity of this dam is gradually decreasing, and it might reach the volume of dead water. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous studies in Algerian watersheds showed the dominance of clockwise hysteresis; it represened 60% of floods in the Kebir West River [24], 37% of floods in Wadi Sebdou [8], and 50% of floods in the Mekerra catchment [15].…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies in Algerian watersheds showed the dominance of clockwise hysteresis; it represened 60% of floods in the Kebir West River [24], 37% of floods in Wadi Sebdou [8], and 50% of floods in the Mekerra catchment [15].…”
Section: Resultsmentioning
confidence: 84%
“…Hysteresis pattern is a graphical tool used to analyze and understand the behavior of sediment concentration in relation to discharge (C-Q) at a specific storm event [3,8,[15][16][17]]. Hysteresis appears when the time lag between the discharge curve and the suspended sediment concentration (SSC) curve is different [18].…”
Section: Introductionmentioning
confidence: 99%
“…This research also calculates statistical information in the rain pattern distribution tests, especially skewness. In summary, Pearson's log model as a statistical model is widely used to analyze flooding in urban areas (Diaf et al, 2020;Szulczewski & Jakubowski, 2018;X. Yang & Wang, 2017) by considering a process approach (Salazar-Galán et al, 2021) and producing several flood scenarios (Farooq et al, 2018;Tian & Wang, 2022).…”
Section: The Prediction Of the Amount Of Flood Probability And Flood-...mentioning
confidence: 99%